Formation, Growth, and Decay of Sea-Ice in the Canadian Arctic Archipelago - Bilello, Michael A. (ARCTIC, 1961)
Equations relating the accretion and decay of sea ice to standard meteorological data are derived empirically from observations at Alert, Eureka, Isachsen, Mould Bay, and Resolute, 1947-1957. The differential equations permit calculation of ice growth by increments, and contain a separate term allowing for variations in snow-cover depths. The use of the formulas requires only a knowledge of air temperatures and snow depths. Good correlation is found between decrease in ice thickness and accumulated degree-days above -1.8°C. The stations' locations and names of adjacent water bodies are indicated with the approximate water depths where ice thickness measurements were made. Techniques used in the measurements are described; data on observed ice thickness, accumulated degree-days of frost, and average snow depths for 20-cm increments of ice growth are tabulated.--From CRREL.